Pengaruh Kualitas Pelayanan, Harga, dan Lokasi Terhadap Kepuasan Konsumen: Studi Kasus di Toko Pertanian Al Mubarok Wonodadi, Kab Blitar - Alfian Dwi Cahya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The farm shop is still considered one of the business sectors that can bring in a lot of profit. Therefore, this research aims to determine the level of service quality, price and location on customer satisfaction at the Al Mubarok Wonodadi Agricultural Shop, Blitar Regency. This study used a non-probability sampling method, namely a saturated sample with a sample of 143 respondents and also used the help of the SPSS application program. The analysis technique used is validity test instrument test, reliability test, classic assumption test, multiple regression test, t test, F test, test of the coefficient of determination. The results of this study indicate that product quality has a partially significant positive effect on customer satisfaction at Al Mubarok Wonodadi Farm Shop, Blitar district, this can be seen from the significant t value of 0.00 <0.05 and service quality, price and location has a partially significant positive effect on customer satisfaction at Al Mubarok Wonodadi Agricultural Shop, Blitar Regency, this can be seen from the significant t value of 0.00 <0.05, while simultaneously service quality, price and location have a significant influence on consumer satisfaction at Al Mubarok Wonodadi Agricultural Shop, Blitar Regency, this can be seen from the significant F value of 0.00 <0.05.